Etyczne aspekty światowego systemu handlowego na przykładzie koncepcji Fair Trade - Grącik-Zajaczkowski, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2015)
The effect of globalization is not only an improvement of living conditions inmany developing countries, but also a widening of development disparities andeconomic inequalities between countries of the rich North and the poor South. Fairtrade can be considered as a response to emerging problems of development.Therefore it is a form of assistance directed to the marginalized producers in theGlobal South by enabling them to manufacture, sell and distribute goods to marketsin developed countries. This is an alternative to the existing formula of internationaltrade, whose aim is to help producers in the South by integrating theminto the current trading system under certain conditions. The idea is to createa new business relationship between producer and consumer, where the productionand consumption are bound together in a new supply chain and where theeconomic benefits are distributed more fairly. It means that the prices of fair tradeproducts are set at a level that would ensure a steady income to the producer andwould lead to raising their living standards and prosperity. The ethical aspects ofthe fair trade system are clear, the problem is whether the fair trade standards canbe used on a wider scale in the global economy, where there is a clash of certainethical values with market economy rules based on maximizing profits and increasingefficiency.